Penerapan Maslahah Mursalah Dalam Transaksi Ekonomi dan Keuangan Kontemporer - Astuti, Sri; Rehan, Muhammad; Afriza, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to provide more in-depth knowledge about the meaning and arrogance of maslahah mursalah and its application in contemporary economic and financial transactions. Maslahah Mursalah is a benefit whose existence is not supported by sharia and is not rejected by sharia through detailed evidences. Maslahah mursalah is a method of legal istinbat that can be accepted by the majority of jurists. The implementation of maslahah mursalah will allow Islamic law to adapt to changes and developments in the modern economy. The implementation of this concept ensures that economic decisions are oriented towards the good and the wider community. In addition, maslahah mursalah can also support the principles of sustainability in the economy. Thus, the application of maslahah mursalah provides practical and adaptive solutions to contemporary economic challenges, without abandoning the fundamental principles of sharia.